Analisis balaghah terhadap ayat Ruqyah Darussyifa’ / Mohd Khairul Akhbar Jahiruddin - Mohd Khairul Akhbar, Jahiruddin (2016)

(untitled)
This study analyzed the Islamic medical treatment or ruqyah syar'iyyah in terms of balaghah Arabic and its types practiced in the Islamic Medical Centre Darussifa. Ruqyah components studied only focused on the 14 Hadith sourced ruqyah and prayer ma'thur, not from the Koran al-Karim. All data was collected from textbooks syllabus used in Darussifa. Ruqyah verses were analyzed based on knowledge which is the Ma‘ani. The study found that there is a unique feature behind balaghah style used in the ruqyah verses and objectives based on the types of diseases and the problem being treated. The study found some kind of force is always used in ruqyah as tawkid style (affirmation), uslub amr, uslub fasl and wasl, the use nakirah and makrifah. Similarly takrar (repetition) which always happens in this ruqyah is an effective cure by reading ruqyah with Allah's permission. The results of this study also prove that the treatment and ruqyah depends on God ultimately